Mimicking acute airway tissue damage using femtosecond laser nanosurgery in airway organoids - Gentemann, Lara; Donath, Sören; Seidler, Anna E.; Patyk, Lara; Buettner, Manuela; Heisterkamp, Alexander; Kalies, Stefan (Frontiers in Cell and Developmental Biology, 2023)
Airway organoids derived from adult murine epithelial cells represent a complex 3D in vitro system mimicking the airway epithelial tissue's native cell composition and physiological properties. In combination with a precise damage induction via femtosecond laser-based nanosurgery, this model might allow for the examination of intra-and intercellular dynamics in the course of repair processes with a high spatio-temporal resolution, which can hardly be reached using in vivo approaches. For characterization of the organoids' response to single or multiple-cell ablation, we first analyzed overall organoid survival and found that airway organoids were capable of efficiently repairing damage induced by femtosecond laser-based ablation of a single to ten cells within 24 h. An EdU staining assay further revealed a steady proliferative potential of airway organoid cells. Especially in the case of ablation of five cells, proliferation was enhanced within the first four hours upon damage induction, whereas ablation of ten cells was followed by a slight decrease in proliferation within this time frame. Analyzing individual trajectories of single cells within airway organoids, we found an increased migratory behavior in cells within close proximity to the ablation site following the ablation of ten, but not five cells. Bulk RNA sequencing and subsequent enrichment analysis revealed the differential expression of sets of genes involved in the regulation of epithelial repair, distinct signaling pathway activities such as Notch signaling, as well as cell migration after laser-based ablation. Together, our findings demonstrate that organoid repair upon ablation of ten cells involves key processes by which native airway epithelial wound healing is regulated. This marks the herein presented in vitro damage model suitable to study repair processes following localized airway injury, thereby posing a novel approach to gain insights into the mechanisms driving epithelial repair on a single-cell level.